Women in Journalism at the Fin de Siècle
XII, 259 p.
Keywords: As the nineteenth-century drew to a close, women became more numerous and prominent in British journalism. This book offers a fascinating introduction to the work lives of twelve such journalists, and each essay examines the career, writing and strategic choices of women battling against the odds to secure recognition in a male-dominated society.